GEOGRAPHICAL FACTORS INCREASING ADMINISTRATIVE-TERRITORIAL ADMINISTRATION EFFICIENCY IN THE REPUBLIC OF ARMENIA (Proceedings of the YSU C: Geological and Geographical Sciences, 2022)
The processes of post-Soviet economic development have raised a number of issues of territorial administration that are directly related to the relationship between society and nature. State-territorial administration starts from territorial administration units, the goal of which is the comprehensive solution of economic, social, environmental, cultural as well as political issues. Since 1995, a new administrative-territorial reform was implemented by the decision of the government, as a result of which 10 Marzes were formed instead of the previous 37 administrative districts. The capital Yerevan received the status of a region and later of a city community. In the Republic of Armenia, the administrative and economic borders have not traditionally coincided. Natural conditions, landscape uplift zones, various natural-geographical characteristics were not taken into account. The modern administrative structure is reminiscent in many respects of the events of the Soviet years, which is proved by comparison. In the conditions of today's transition economy, the practical significance of economic regionalization is to acquire new content, quality in line with market relations. These have raised a number of issues, which are divided into the following problems: socio-economic, geographical, political, demographic. It should be noted that the mentioned issues of territorial administration coincide with the socio-economic and political situation in the RA. Scientific and practical recommendations of science are useful for the systematic and effective development of state territorial administration and should be taken into account by public administration bodies, in particular, departments of territorial administration.
Keywords: territorial administration; administrative-territorial structure; territorial reform; optimization; administrative border; border settlement; high mountain settlement